The investigation of molecular epidemiological characteristics and resistance mechanism of tigecycline resistant Klebsiella pneumoniae from a large teaching hospital in southwest China, Chongqing - Li, Yuqiong; Tang, Shiyu; Han, Qi; Xia, Peiwen; Si, Tingting; Song, Yuanyuan; Xia, Yun (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundKlebsiella pneumoniae is one of the main pathogens of nosocomial infection, among which carbapenems can be used for multidrug-resistant Klebsiella pneumoniae. However, in the past decade, the resistance rate of carbapenem-resistant Klebsiella pneumoniae has increased yearly. Tigecycline has good antibacterial activity in treating severe bacterial infections, but the reports of tigecycline resistance are increasing. This study aimed to investigate the mechanism of drug resistance and epidemiological characteristics of tigecycline-resistant Klebsiella pneumoniae (TRKP) in a large teaching hospital in southwest China, Chongqing.MethodsWe isolated 30 TRKP strains from this hospital between August 2021 and December 2023. By PCR and sequencing, we examined the presence and mutation rates of genes associated with tigecycline resistance, including acrR, oqxR, ramR, tmexC, tet(x), tet(A), tet(L), and rpsj, and performed efflux pump inhibition experiments to verify efflux pump activity. At the same time, real-time RT-PCR was used to detect the expression levels of efflux pump genes (acrB and oqxB) and ramA. To investigate the prevalence trend of TRKP in our hospital, we performed multi-site sequence typing (MLST) analysis.ResultsThe mutation rates of ramR (73.3%) and tet(A) (63.3%) were significant. In efflux pump inhibition experiments, PaβN could reverse the resistance of 29 TRKP strains (96.7%) to tigecycline. Real-time RT-PCR results showed that acrB and ramA genes were up-regulated in 22 strains, while oqxB genes were overexpressed in only 4 strains. MLST analysis showed that these strains could be divided into 25 different ST subtypes, indicating that no outbreak of TRKP occurred in our hospital. In addition, two tmexCD-torpj positive strains, ST661 and ST1561, were identified for the first time.ConclusionThe efflux pump acrB and tet(A) mutations are the primary mechanisms of resistance to tigecycline-resistant Klebsiella pneumoniae at our hospital. The ramR mutation can mediate efflux pump activity of acrB by up-regulating ramA overexpression.